Challenging Southeast Asian development the shadows of success - Rigg, Jonathan 1959- (Routledge, Taylor & Francis Group, 2016)
"Over the course of the last half century, the growth economies of Southeast Asia, Indonesia, Malaysia, the Philippines, Singapore, Thailand and Vietnam, have transformed themselves into middle income countries. This book looks at how the very success of these economies has bred new challenges, novel problems, and fresh tensions, including the fact that particular individuals, sectors and regions have been marginalised by these processes"--Provided by publisher.